ANALISIS EFEKTIVITAS BIAYA BEBERAPA MOISTURIZER - Dasopang, Eva Sartika; Hasanah, Fenny; Siahaan, Desy Natalia; Salsabila, Putri (Jurnal Riset Kefarmasian Indonesia, 2024)
The growth of e-commerce continues to increase in Indonesia, one of which is the Shopee application which can buy goods, sell various kinds of products, and shop safely. Shopee showed in early 2020 that the beauty category ranked highest in the best-selling product categories, one of which was Moisturizer. The purpose of this study was to determine the comparison of each moisturizer which is more cost effective. This type of research uses a true experimental method with a posttest only control group design to determine the before and after conditions between the control group (no moisturizer) and the experimental group (moisturizer X, moisturizer Y, moisturizer Z). The sample of this study consisted of 20 volunteers with observations carried out for 4 weeks to obtain the effectiveness of moisture recovery, pores, blemishes, wrinkles. The results showed that moisturizer Z for moisture is more cost effective with an ACER value of Rp. 859 ICER Rp. 886. While moisturizer Y for pores is more cost effective with an ACER value of Rp. 2,515 ICER Rp. 2,800. While moisturizer Y for blemishes is more cost effective with an ACER value of Rp. 2,427.7 ICER Rp. 2,581. Then moisturizer Z for wrinkles is more cost effective with an ACER value of Rp. 1,846 ICER Rp. 2,307. In conclusion, moisturiser C is the most cost effective for moisture and wrinkles while moisturiser B is more cost effective for pores and blemishes.